2019
DOI: 10.1002/cam4.2767
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases and immunosuppressive therapy in relation to the risk of glioma

Abstract: Effectors from the immune system can modulate the course and possibly the early development of gliomas. We, therefore, hypothesized that autoimmune diseases associated with increased immune-surveillance may also modulate the risk of human glioma. To test this hypothesis, we used data from the well-validated Clinical Practice Research Datalink (CPRD) GOLD from the UK to analyze the association of immune-related disorders or use of immunosuppressive drugs and the risk of glioma. We identified 3112 incident gliom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Lastly, the findings described in this report add to a growing literature implicating T lymphocyte in brain function, including learning 40 , 41 social behavior 42 , 43 and neurodegeneration in the setting of neuronal injury 44 , 45 . In this manner, it is conceivable that other systemic conditions involving T lymphocytes, such as eczema 26 , 46 , 47 , rheumatoid arthritis 48 , 49 , and diabetes 50 , 51 , may similarly impact gliomagenesis through overlapping or related mechanisms. Defining the molecular etiologies underlying how these T cell-mediated systemic conditions influence brain function and nervous system disease pathogenesis may also reveal unique immunomodulatory treatment strategies for neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the findings described in this report add to a growing literature implicating T lymphocyte in brain function, including learning 40 , 41 social behavior 42 , 43 and neurodegeneration in the setting of neuronal injury 44 , 45 . In this manner, it is conceivable that other systemic conditions involving T lymphocytes, such as eczema 26 , 46 , 47 , rheumatoid arthritis 48 , 49 , and diabetes 50 , 51 , may similarly impact gliomagenesis through overlapping or related mechanisms. Defining the molecular etiologies underlying how these T cell-mediated systemic conditions influence brain function and nervous system disease pathogenesis may also reveal unique immunomodulatory treatment strategies for neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…18 Studies indicated that the onset age of glioma is mostly between 21 and 50 years old, and the peak is between 31 and 40 years old. 19 However, with the change of life habits and the increase of life pressure, the incidence of glioma in recent years has become younger population, which caused widespread concerns. 20 At present, the difficulties in the treatment of glioma lie are rapid progression, poor prognosis and high postoperative recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only known environmental factor linked to primary brain cancer is ionizing radiation [ 9 ]. Recently, there has been increased investigation between the relationship of anti-TNF therapies and glioblastoma multiforme (GBM), the most aggressive type of primary brain cancer with a reported median survival time of 15-20.9 months from the time of diagnosis [ 5 , 9 ]. It has been suggested that infliximab and adalimumab have a stronger association with GBM compared to other anti-TNF agents [ 5 ].…”
Section: Introductionmentioning
confidence: 99%